PENGARUH INTERNET FINANCIAL REPORTING TERHADAP KINERJA SAHAM - M.Riduan Abdillah; Astia Putriana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract This research aims to find empirical evidence of the effect of Internet Financial Reporting (IFR) on stock performance with firm size as a control variable. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange in 2020. The sampling technique of this research used the purposive sampling method. This research method is a quantitative method. The dependent variable in this research is stock performance, while the independent variable in this research is Internet Financial Reporting (IFR) while firm size is the control variable. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2020. The data analysis of this research uses multiple linear regression. The results of this research found empirical evidence that Internet Financial Reporting (IFR) has an effect on stock performance while firm size as a control variable has a significant effect on stock performance. Keywords : Internet Financial Reporting (IFR), company size, stock performance